Arterial and venous thrombosis following trauma and major orthopedic surgery: molecular mechanisms and strategies for intervention - Dahl, Ola E.; Harenberg, Job (Seminars in thrombosis and hemostasis, 2015)
A variety of harmful effects can be triggered by trauma and major orthopedic surgery. One of the key players involved in this process is thrombin. The clinical consequence of this process has, for several decades, been considered to be formation of deep vein thrombosis and pulmonary embolism. Controlling thrombin generation and activation has therefore been the goal of thromboprophylaxis regimens administered to patients suffering from trauma or undergoing major surgery. Protecting patients from venous thromboembolism has, for many years, been the main goal of preventive strategies. However, our knowledge of cell destruction and release of substances that may cause organ damage has expanded in recent years. Release of molecules such as RNA and histones from destroyed tissues may cause cell destruction and organ damage at distal sites if released in huge amounts and disseminated systemically. This new knowledge points toward an unmet need for therapies that prevent both vascular events and organ deterioration. This article briefly reviews molecular mechanisms associated with the occurrence of vascular events and cellular destruction in patients with major bone damage caused by trauma.
Gesehen am 25.09.2017